If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -17 = 6x + 7 Reorder the terms: -17 + 7x = 6x + 7 Reorder the terms: -17 + 7x = 7 + 6x Solving -17 + 7x = 7 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -17 + 7x + -6x = 7 + 6x + -6x Combine like terms: 7x + -6x = 1x -17 + 1x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 -17 + 1x = 7 + 0 -17 + 1x = 7 Add '17' to each side of the equation. -17 + 17 + 1x = 7 + 17 Combine like terms: -17 + 17 = 0 0 + 1x = 7 + 17 1x = 7 + 17 Combine like terms: 7 + 17 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| (X+6)+x+2x=35 | | .333x-4=2 | | 2*(y^2)-x^2=0 | | -2(12)+12y=47 | | -16x+7=-41 | | -2(-12)+12y=47 | | 2(x+7)+3(x-5)= | | .09X+X=100 | | -48-12x=8 | | -2(-2)+12y=47 | | 7n-3n=19 | | 4i^5= | | -2c(-c-12)=-2c-12 | | -5(7x-9)=-35x+45 | | -8x-2=-x+3 | | 368=-7x+8(-5x-1) | | 5i^10= | | 15cos^2+(4cos)-3=0 | | 2y+4=-2x+6 | | 4x^2-60x-70=0 | | 6y=18x+36 | | (2+3i)(5-3i)(-7+I)= | | 6+4=-5 | | 6x-4=-50 | | (4+6i)-(5+3i)= | | 4x+4=29 | | x*7+46=221 | | 1.4(0.1)-0.1y=-7.9 | | 1.4(1.4)-0.1y=-7.9 | | -0.3x+9.79=-0.1x+3.39 | | 5x-10=38 | | x-40=-45 |